2020
DOI: 10.1007/jhep03(2020)094
|View full text |Cite
|
Sign up to set email alerts
|

Precise determination of αs from relativistic quarkonium sum rules

Abstract: We determine the strong coupling α s (m Z ) from dimensionless ratios of roots of moments of the charm-and bottom-quark vector and charm pseudo-scalar correlators, dubbed R X,n q ≡ (M X,n q ) 1 n /(M X,n+1 q ) 1 n+1 , with X = V, P , as well as from the 0-th moment of the charm pseudo-scalar correlator, M P,0 c . In the quantities we use, the mass dependence is very weak, entering only logarithmically, starting at O(α 2 s ). We carefully study all sources of uncertainties, paying special attention to truncatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 91 publications
3
36
1
Order By: Relevance
“…Their use in the case of the vector current was introduced in refs. [10,11] where it was shown that they can be employed for precise extractions of α s thanks to their reduced mass dependence and to the fact that these ratios can be accurately determined from R qq (s) experimental data, benefiting from positive correlations between the moments M V q,n and M V q,n+1 . The general structure of the perturbative expansion of the moments R δ q,n is…”
Section: Jhep08(2021)027mentioning
confidence: 99%
See 3 more Smart Citations
“…Their use in the case of the vector current was introduced in refs. [10,11] where it was shown that they can be employed for precise extractions of α s thanks to their reduced mass dependence and to the fact that these ratios can be accurately determined from R qq (s) experimental data, benefiting from positive correlations between the moments M V q,n and M V q,n+1 . The general structure of the perturbative expansion of the moments R δ q,n is…”
Section: Jhep08(2021)027mentioning
confidence: 99%
“…At the scales we consider here, the ambiguity of the Borel integral is numerically quite small, as we will show in the next sections, which simply reflects the fact that the non-perturbative corrections in the OPE, dominated by the gluon condensate contribution, are rather small. This is particularly true for bottom quark moments, where the non-perturbative contributions can be neglected for all practical purposes [9,11].…”
Section: Jhep08(2021)027mentioning
confidence: 99%
See 2 more Smart Citations
“…There are indications that bulk theory has an infinite number of local fields [20]. Furthermore, since the theory lacks a gap in its spectrum and owing to bounds on the branching time, sub-AdS locality might be absent [21]. These two features bear resemblance to higher spin gravity theories in AdS.…”
Section: Introductionmentioning
confidence: 99%